ANALISIS MANAJEMEN STRATEGI PADA PT. PLN (PERSERO) (Studi Kasus UPJ Garut Kota - Kabupaten Garut) - Erna Rustiana; Hedi Cuapiadi (Jurnal Ekonomi Dan Bisnis, 2017)
In performing the internal activity of PT. PLN (Persero) UPJ Garut Kota necessary arrangements efficiently and effectively to achieve organizational orientation towards customer satisfaction and to achieve the Vision, Mission and Objectives of the company. A detailed analysis regarding the company's goal to explain ideas and show how its suitability in determining the basis for the company of the strategic situation faced by the company. Strategy program PT. PLN (Persero) UPJ Garut Kota based company's national strategy which is based on government policy on electricity in Indonesia. In the implementation adapted to the circumstances and conditions of the company that has Strength and Weakness, Opportunity of internal organization, and Threats of external Organizations.Keyword: Strategic Management, Customer Satisfaction, SWOT Analysis